2008
DOI: 10.1016/j.cub.2008.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Memory in Caenorhabditis elegans Is Mediated by NMDA-Type Ionotropic Glutamate Receptors

Abstract: Learning and memory are essential processes of both vertebrate and invertebrate nervous systems that allow animals to survive and reproduce. The neurotransmitter glutamate signals via ionotropic glutamate receptors (iGluRs) that have been linked to learning and memory formation; however, the signaling pathways that contribute to these behaviors are still not well understood. We therefore undertook a genetic and electrophysiological analysis of learning and memory in the nematode Caenorhabditis elegans. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 47 publications
(54 reference statements)
5
63
0
Order By: Relevance
“…The first experiment was conducted using MK801, a non-competitive antagonist of the N-methyl D-aspartate glutamate receptors (NMDAR). This drug has been widely used as anamnesic agent in several memory tasks in different species (Morris et al 1986;Tan et al 1989;Miserendino et al 1990;Lin and Glanzman 1994;Rickard et al 1994;Weldon et al 1997;Gutiérrez et al 1999;Roberts and Glanzman 2003;Si et al 2004;Xia et al 2005;Wu et al 2007;Kano et al 2008;Müssig et al 2010;Rosenegger and Lukowiak 2010;Amano and Maruyama 2011). Moreover, MK801 caused amnesic effects in consolidation (Troncoso and Maldonado 2002), reconsolidation and extinction (Pérez-Cuesta and Maldonado 2009) in Chasmagnathus, consistent with the presence of NMDAR in the crab CNS (Hepp et al 2013).…”
Section: Inhibition Of the Ups Blocks The Action Of Mk801 And Bicuculmentioning
confidence: 80%
“…The first experiment was conducted using MK801, a non-competitive antagonist of the N-methyl D-aspartate glutamate receptors (NMDAR). This drug has been widely used as anamnesic agent in several memory tasks in different species (Morris et al 1986;Tan et al 1989;Miserendino et al 1990;Lin and Glanzman 1994;Rickard et al 1994;Weldon et al 1997;Gutiérrez et al 1999;Roberts and Glanzman 2003;Si et al 2004;Xia et al 2005;Wu et al 2007;Kano et al 2008;Müssig et al 2010;Rosenegger and Lukowiak 2010;Amano and Maruyama 2011). Moreover, MK801 caused amnesic effects in consolidation (Troncoso and Maldonado 2002), reconsolidation and extinction (Pérez-Cuesta and Maldonado 2009) in Chasmagnathus, consistent with the presence of NMDAR in the crab CNS (Hepp et al 2013).…”
Section: Inhibition Of the Ups Blocks The Action Of Mk801 And Bicuculmentioning
confidence: 80%
“…Testing candidate mutants of various upstream regulators, Fu et al (2009) showed that salt conditioning activated DKF-2 via a pathway containing EGL-8, a DAG-producing PLC-b4 homolog and TPA-1, a DAG-activated PKC d-u homolog. Kano et al (2008) proposed that retention of the learned NaCl aversion requires the NMDA receptor subunits, NMR-1 and NMR-2. Both nmr-1 and nmr-2 mutants learned to avoid NaCl after it was paired with starvation, but when left on the assay plate, these mutants accumulated at the NaCl point source more quickly than wild-type worms.…”
Section: Taste As the Conditioned Stimulusmentioning
confidence: 99%
“…There were no differences between the responses of training and testing if nmr-1; Pnmr-1::nmr-1 worms were trained and tested in different contexts (no odor-C 4 H 6 O 2 or C 4 H 6 O 2 -no odor; P > 0.05). Kano et al (2008) showed that, in C. elegans, rescuing the NMDA receptor subunit NMR-1 in the pair of RIM interneurons was critical for taste associative learning (starvation and taste association). To see whether expression of NMR-1 in the RIM interneurons was sufficient to rescue short-term olfactory context conditioning in nmr-1 mutant worms, we injected a construct in which the NMR-1 cDNA was under the regulation of the tdc-1 promoter (Ptdc-1::NMR-1) into nmr-1 mutant worms (Kano et al 2008).…”
Section: Nmda-type Glutamate Receptor Subunit Nmr-1mentioning
confidence: 99%